2014
DOI: 10.1179/2295333714y.0000000057
|View full text |Cite
|
Sign up to set email alerts
|

A nephrotic syndrome of tropical origin: case report and short review of the aetiology

Abstract: We present a case of nephrotic syndrome in a 38-year-old man of Ivorian origin. In the search of the cause of his illness an infection with Plasmodium malariae (P. malariae) was diagnosed by serology and by microscopy of a Giemsa thin blood smear which revealed rare gametocytes of P. malariae. Proteinuria significantly diminished within three months after antimalarial treatment. Antibodies against Schistosoma were detected as well. Examination of kidney biopsy revealed a discrete mesangioproliferative glomerul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…malariae infection, is mostly described in children living in endemic areas [ 32 ] with few cases reported since the mid-1970s [ 32 34 ]. Renal biopsies in two recent cases have shown chronic membranous glomerulopathy [ 34 ] and mesangioproliferative glomerulonephritis respectively [ 33 ]. The syndrome has been reported as being hard to treat and often unresponsive to corticosteroids, immunosuppressive agents and antimalarial drugs [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…malariae infection, is mostly described in children living in endemic areas [ 32 ] with few cases reported since the mid-1970s [ 32 34 ]. Renal biopsies in two recent cases have shown chronic membranous glomerulopathy [ 34 ] and mesangioproliferative glomerulonephritis respectively [ 33 ]. The syndrome has been reported as being hard to treat and often unresponsive to corticosteroids, immunosuppressive agents and antimalarial drugs [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophilia has been associated with nephrotic syndrome in the context of parasitic infestations in the tropics. 8 In a large biopsy-based series of 2,827 patients with renal disease, it was found that 10% to 21% of patients had associated eosinophilia and amongst membranous glomerulonephritis, 14.4% had eosinophilia. 9…”
Section: Eosinophilia and Nephrotic Syndromementioning
confidence: 99%
“…The parasite density is always low compared to Plasmodium falciparum and it produces clinical relapses due to the asexual forms that persist in the host's blood [17]. Symptoms include nephropathies [19][20][21][22][23], a long asymptomatic persistence of several years before access to recrudescence [24] that may induce transfusional malaria [25], genetic polymorphism [26][27][28][29], transmission by palearctic or tropical vectors [30,31], and due to its possibility to infect human and simian subjects [32], it was considered as an anthropozoonosis.…”
Section: Introductionmentioning
confidence: 99%